A characterization for Adams-type boundedness of the fractional maximal operator on generalized Orlicz–Morrey spaces. Issue 4 (3rd April 2017) - Deringoz, Fatih; Guliyev, Vagif S.; Hasanov, Sabir G.
ABSTRACT: In the present paper, we shall give a characterization for weak/strong Adams-type boundedness of the fractional maximal operator on generalized Orlicz–Morrey spaces.